A role for programmed cell death in the microbial loop. - Mónica V Orellana (Public Library of Science (PLoS), 2013)
The microbial loop is the conventional model by which nutrients and minerals are recycled in aquatic eco-systems. Biochemical pathways in different organisms become metabolically inter-connected such that nutrients are utilized, processed, released and re-utilized by others. The result is that unrelated individuals end up impacting each others' fitness directly through their metabolic activities. This study focused on the impact of programmed cell death (PCD) on a population's growth as well as its role in the exchange of carbon between two naturally co-occurring halophilic organisms. Flow cytometric, biochemical, ¹⁴C radioisotope tracing assays, and global transcriptomic analyses show that organic algal photosynthate released by Dunalliela salina cells undergoing PCD complements the nutritional needs of other non-PCD D. salina cells. This occurs in vitro in a carbon limited environment and enhances the growth of the population. In addition, a co-occurring heterotroph Halobacterium salinarum re-mineralizes the carbon providing elemental nutrients for the mixoheterotrophic chlorophyte. The significance of this is uncertain and the archaeon can also subsist entirely on the lysate of apoptotic algae. PCD is now well established in unicellular organisms; however its ecological relevance has been difficult to decipher. In this study we found that PCD in D. salina causes the release of organic nutrients such as glycerol, which can be used by others in the population as well as a co-occurring halophilic archaeon. H. salinarum also re-mineralizes the dissolved material promoting algal growth. PCD in D. salina was the mechanism for the flow of dissolved photosynthate between unrelated organisms. Ironically, programmed death plays a central role in an organism's own population growth and in the exchange of nutrients in the microbial loop.